A presença de metais pesados em produtos cosméticos e o papel do engenheiro químico nas boas práticas de fabricação - Melo, Jaqueline Aparecida de (Universidade Federal de São Carlos, 2023)
Various metals are found in nature. Some are essential for health, others are harmful. Heavy metals can be present in contaminated water, soil and food, resulting in health problems over the years. However, many people do not know that these metals can even be present in cosmetic products, such as skin creams, deodorants, lipsticks and other makeup, for example. They can be incorporated into cosmetic products with an established purpose or be found in the form of impurities. Normally, heavy metals do not cause serious symptoms the first time they come into contact with the body, but this is different in the long term. Due to their ability to accumulate in cells, they cause problems such as kidney changes, brain injuries, cardiovascular and reproductive complications, and may even be related to the incidence of cancer. In Brazil, ANVISA is the regulatory body responsible for defining and monitoring the maximum permitted limit of heavy metals in cosmetic products. As it is a very small amount, it is not necessary to include them in the product's ingredients list. Therefore, companies and laboratories must follow Good Manufacturing Practices (GMP) standards to reduce the impact caused by these heavy metals, using only the maximum amount allowed and thus preventing contamination of consumers. The basic GMP requirements constitute an important field of activity for the chemical engineer. Therefore, this work seeks to survey the literature regarding the main heavy metals found in cosmetics, the consequences on consumer health and the environment. Describe techniques that identify and quantify their presence, current legislation, historical evolution and relevance of the cosmetics market in Brazil. Also, present the Good Manufacturing Practices for cosmetic products, the requirements for documentation, equipment, personnel, inputs and facilities, and the role of the chemical engineer in GMP. A case study will be presented to understand lipstick contamination by heavy metals. From the analysis of the lipstick production process and the raw materials used, it was found that the main origin of this contamination is in the pigments used. Concluding, then, that the use of Good Manufacturing Practices requirements regarding raw materials, required by ANVISA, are fundamental to mitigating this problem.
The presence of heavy metals in cosmetic products and the role of the chemical engineer in good manufacturing practices
Keywords: Produtos cosméticos; Metais pesados; Boas práticas de fabricação; Batom; Cosmetic products; Heavy metals; Good Manufacturing Practices (GMP); Lipstick; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA